Analisis Nilai Religius dalam Cerita Perang Obor di Jepara - Janita Putri Dwihana; Aulia Tri Lestari; Nida Dhiyaul Auliyah; Mohammad Kanzunnudin (Universitas Palangka Raya, 2025)
This article discusses the religious values contained in the Torch War folktale from Tegalsambi Village, Jepara. This story is not only part of the cultural heritage of the community, but also contains strong spiritual values, such as gratitude to God, the implementation of religious rituals, and the spirit of togetherness among residents. This research was conducted with a qualitative approach and used the hermeneutic method to explore the symbolic meaning and socio-religious role of the story. The findings indicate that the Torch War reflects a harmonious blend of local culture and Islamic values, known as Islam Nusantara. The religious values in this story play an important role in strengthening the identity of the community and maintaining harmony in everyday life. These values help preserve the local traditions while integrating religious practices, fostering unity, and ensuring the sustainability of cultural and spiritual life in the community. This study highlights how folklore serves as a medium for transmitting religious and cultural teachings across generations.